Optimization of geothermal energy extraction from abandoned oil well with a novel well bottom curvature design utilizing Taguchi method - Cheng, S.W.Y. (Elsevier Ltd, 2019)
Abandoned oil wells have a great potential to be converted into geothermal energy extraction wells. However, these wells have low energy conversion rates as compared to conventional geothermal open loop wells. Therefore, increasing the heat transfer is one of the major concerns in the utilization of abandoned oil well for geothermal energy extraction. This study is conducted to evaluate the heat transfer enhancement of a novel well bottom curvature design installed inside the wellbore using a computational fluid dynamics approach. Various well bottom curvature designs were evaluated, along with the effects of working fluid inlet temperature and flow rate. For optimization, Taguchi Statistical Method was adopted to determine the optimum parameter combination and their interactions. From the study, it is found that 0.5 m well bottom curvature is preferred for higher output temperature and heat transfer rate, whereas 0.8 m well bottom curvature is recommended for lowering pressure drop and producing higher CoP. On the other hand, lower injection temperature (288K) and lower injection rate (10 m3/h) produces better overall wellbore performance, except for higher outlet temperature purposes, where a higher injection temperature (298K) is favoured and higher heat transfer rate applications, where a higher injection rate (30 m3/h) is preferred. Â© 2019